Roman Faith and Christian Faith - Morgan, T (Cambridge University Press, 2018)
These three short papers were delivered at the 72nd General Meeting of the Studiorum Novi Testamenti Societas, held in Pretoria, South Africa, on 8–11 August 2017. The ‘Quaestiones disputatae’ session was chaired by the President of the Society, Professor Michael Wolter. The first two papers engage with Teresa Morgan's book, Roman Faith and Christian Faith, and Professor Morgan responds to them in the third.